AKUNTANSI LINGKUNGAN SEBAGAI STRATEGI PENGELOLAAN DAN PENGUNGKAPAN TANGGUNG JAWAB LINGKUNGAN PADA PERUSAHAAN MANUFAKTUR - Pratiwi, Wahyu Mega (Jurnal Akuntansi AKUNESA, 2013)
The impact of manufactory activites in our planet is getting worse. Global Warming is the most popular issue in the environmental problem. Environmental accounting is on an expansion path. With increasing social focus on the environment, accounting fills an expectation role, to measure environmental performance. This paper tries to describe about the relationship of environmental accounting as environmental management strategy and disclosure of environmental accountability strategy in order to determine the sustainability of corporate. Keywords: manufactory, environtment, accounting